2014
DOI: 10.1002/jcb.24756
|View full text |Cite
|
Sign up to set email alerts
|

Expression of P2X7 ATP Receptor Mediating the IL8 and CCL20 Release in Human Periodontal Ligament Stem Cells

Abstract: ATP is released by human periodontal ligament cells (hPDLCs) and has been shown to regulate PDL regeneration and responses to mechanical stress through activation of P2Y receptors. This nucleotide, however, has also been reported to trigger the pro-inflammatory cascade by inducing the maturation and/or release of chemokines/cytokines from various cell types mainly via P2X7 receptors. Much less is known on the possible role of ATP in stem cells deriving from PDL (hPDLSCs) which are considered to be a promising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…Human periodontal ligament stem cells (hPDLCs) released CXCL8 following extended stimulation of the P2X7R, involving an increase in intracellular Ca 2+ concentrations [147]. CXCL8 release from human neutrophils was stimulated synergistically by toll-like receptors and P2Rs.…”
Section: Inflammatory Chemokines(c-c Motif) Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human periodontal ligament stem cells (hPDLCs) released CXCL8 following extended stimulation of the P2X7R, involving an increase in intracellular Ca 2+ concentrations [147]. CXCL8 release from human neutrophils was stimulated synergistically by toll-like receptors and P2Rs.…”
Section: Inflammatory Chemokines(c-c Motif) Ligandsmentioning
confidence: 99%
“…Chemokine production was mediated via both calcineurindependent nuclear factor of activated T cells (NFAT) and PKC/MAPK signaling pathways. Similar to CXCL8, stem cells derived from human periodontal ligament cells released CCL20 (also macrophage inflammatory protein-3, MIP3A), a chemoattractant for lymphocytes and neutrophils, through P2X7R activation [147].…”
Section: Inflammatory Chemokines(c-c Motif) Ligandsmentioning
confidence: 99%
“…In terms of infection, ATP is a well-recognized signaling molecule released at sites of inflammation/cell injury, and plays a central role in immune cell migration, chemotaxis, and cytokine release (Junger, 2008; Bours et al, 2011). In particular, the P2X 7 receptor has attracted considerable attention for its importance in immune cell communication (Di Virgilio and Vuerich, 2015), release of pro-inflammatory cytokines (Suzuki et al, 2004; Clark et al, 2010; Shieh et al, 2014; Trubiani et al, 2014), and recruitment of macrophages and lymphocytes (Moncao-Ribeiro et al, 2011; da Silva et al, 2013). Therefore, the P2X 7 has emerged as a potential anti-inflammatory therapeutic target.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, bacterial eATP‐induced chemokine expression occurred in a PLC‐independent manner, indicating a role for the P2X receptor. A recent report showed that ATP induced the expression of chemokine in human periodontal ligament stem cells (Trubiani et al ., ). Similarly, we found that bacterial eATP P2X7 receptor was important in sensing bacterial eATP to elicit a chemokine response.…”
Section: Discussionmentioning
confidence: 97%